Design of the MCCIS on the Gas- fueled motorcycle to overcome detonation in engine idling / Didik Nurhadiyanto...[et al.] - Nurhadiyanto, Didik; Mujiyono,, Angger Gufita; Riyadi, Prabowo Moecty; Baihaqi, Fatchurrohman; Pramana, Sena Budi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Gasoline consumption is greater than fuel oil production in Indonesia. The situation has come to that of a fuel oil crisis. Prior research indicates that the exhaust gas emission of motorized vehicles using gasoline contains lead still as heavy metal. The problem with vehicles using fuel gas is that with the engine ignited and left idling detonation occurs because the gas supply is great while the air supply is small. In addition, the gas tank posible to explodes when sparks come from the combustion chamber. The objective of the research concerned here was to design the Mechanics Converter Considering Idle System (MCCIS) to overcome the problem of detonation at the time of engine idling, to design a flame arrester to prevent an exploding gas tank, and to testing the exhaust gas emission. The MCCIS may be used on low or high speed motorcycles using fuel gas. No detonation occurred in idle speed throughout. The flame arrester was able to avoid the sparks so the fire wasn't moving into the gas tank. Results of the exhaust gas emission tests indicate that exhaust gas emissions at idling, moderate and high speeds are included in the CO and HC content of the specified magnitude.